Prediction and Evaluation of Water Resource Ecological Footprint in Beijing under the Influence of Changing Environment - QIN Huanhuan; HUANG Lixiang; WANG Jianquan (Renmin Zhujiang)
Ten sub-categories of scenarios are designed based on the system dynamics model for water resource utilization in Beijing to predict and evaluate the water resource ecological footprint in Beijing from 2022 to 2030 under the influence of changing environment.The results show that:① From 2022 to 2030,the water resource ecological footprint per capita under each scenario shows a downward trend (except for the scenario CC-wet),with an average value of 0.414~0.475 hm2 per capita.The water resource ecological carrying capacity per capita shows a downward trend,with an average value of 0.101~0.139 hm2 per capita.The average value of water resource ecological deficit per capita is 0.293~0.367 hm2 per capita.The water resource ecological pressure index shows a fluctuating trend,with an average value of 3.225~4.608,and Beijing will face the situation of water resource unsafe utilization.The water resource ecological footprint intensity shows a significant downward trend,with an average of 0.013~0.024 hm2/104 RMB,and the water resource utilization efficiency in Beijing is constantly improving.② As the climate is wetter,the ecological footprint,ecological deficit,ecological pressure,and ecological footprint intensity of water resources are smaller in Beijing and vice versa.③ Rapid economic development has a significant influence on the ecological footprint,ecological carrying capacity,ecological deficit,and ecological pressure index of water resources.The South-to-North Water Diversion Project (SNWDP) has an immediate effect on reducing the ecological footprint and ecological deficit of water resources.Water saving in animal husbandry has a small influence on the indicators related to the water resource ecological footprint.④ In its future development,Beijing should consider both economic development and water resource protection,take measures to deal with the possible influence of climate change,make full use of the SNWDP in promoting the sustainable use of water resources,and constantly improve the awareness of water conservation and the efficiency of production and domestic water use in the whole society,promoting the sustainable development and utilization of social economy and water resources in the capital through multi-pronged efforts.